THE EFFECT OF TEACHER MOTIVATION, COMPENSATION, AND WORKLOAD ON TURNOVER INTENTION THROUGH JOB SATISFACTION AS A MEDIATING VARIABLE - Anwar, Yohny; Suwarno, Bambang; Harianti, Suci (Universitas Brawijaya, Indonesia, 2023)
This study aims to determine and analyze the effect of motivation, compensation Â and workload on turnover intention with job satisfaction as an intervening variable for Non-Permanent Teachers at SMA Negeri 1 Sinunukan, Mandailing Natal, North Sumatra. This research uses a causal research method with a quantitative approach. Forty teachers made up the total population of the research sample, which was selected using a saturation sampling technique and non-probability sampling. approaches for gathering data that are tested for validity and reliability utilizing interviews and questionnaires. Analyzing data using SEM-PLS. The results of the study show that motivation has a significant positive effect on turnover intention through job satisfaction; The variable job satisfaction mediates motivation on turnover intentions. Then for compensation has a significant positive effect on turnover intention through job satisfaction; Variable of job satisfaction mediates compensation to turnover intention. Likewise, the effect of workload on turnover intention through job satisfaction as an intervening.